ڕەهەندە ئابووریەکانى ڕێکەوتننامەى سایکس - پیکۆ - حسن, قادر محمد (Sulaimani Journal for Humanities, 2018)
ABSTRACT The Sykes-Picot secret agreement signed by Britain, France, Tsarist Russia, representatives of the sixteenth of May of 1916, which remained under wraps until ripen the surrounding circumstances, and calm down the region that were experiencing significant political developments during the First World War. France had cost the agreement was signed George W. Pico Consul former in Beirut and high commissioner to follow the Near Eastern Affairs, while such as Britain's Sir Mark Sykes traveler and orientalist and the British High Commissioner for Near Eastern Affairs, was the role of the Russian delegate Sazanov overseeing the negotiations between the two countries, those negotiations took place in Cairo and then I moved to another yard further from the East were not only Russian city of St. Petersburg. Search the subject of this agreement very much in the political aspects and diplomacy as well as the results that emerged after the end of World War, but we believe that the economic aspect of the agreement need to further study and analysis, so we have dedicated this research to clarify the economic factors that have had a major role in shaping policy applied as a result of an agreement .bgesna on the subject of oil, and the British and French ambitions in the oil state of Mosul and control of the roads and the possession of the goods and the economies of the region, particularly in South Kurdistan and decides that Palestine is under an international administration to be agreed upon in consultation between Britain, France and Russia. But the text of the agreement to give Britain the ports of Haifa and Acre to be France's freedom to use the port of Haifa, and was awarded France to Britain in return the use of the port of Iskenderun, which was falling in their possession. At the end of the research were presented research results on the role of the economy in the drafting of the Convention, and even though their application was not in the same context that was unanimously agreed during the war.